A ética no trabalho do assistente social : análise das particularidades das denúncias em Sergipe - Oliveira, Ilma Cristina Silva (2016)
The present study had as objective to analyze the origin and cause of complaints about ethical irregularities on the professional practice of social worker, submitted to CRESS 18ª region. In this sense, the debate went around the operational dimension of ethics guided by the principles and ideals that consubstantiated each professional Code of Ethic. Concerning to methodological procedures, it’s a documental and bibliographic research with and qualitative approach, utilizing as technique the analyses of complaints filed in CRESS Sergipe, as well as the laws that govern the ethical dimension of Social Work. The research universe consists of 18 complaints filed in CRESS in time frame of 14 years. This study initially presents a reflexion about social work historical journey and the ideals which guided seizure of professional ethics. Then, it shows the place of ethics in contemporary Social Work with the backdrop of the Political Ethics Project, a result from the process of maturity and professional position from the ethical principles such as democracy, liberty, equality and citizenship and uncompromising defense of social rights. inally, it was found that the complaint as a public instrument of defense of the "interests" of the user and the profession, is presented as a possibility to observe the ethical and technical working conditions, guarantee the quality of provision of social services critically and zeal in the defense of human rights.